2016
DOI: 10.1002/cphc.201600120
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Stability of Transition‐Metal‐Substituted LiMn2−xMxO4 (M=Cr, Fe, Co, and Ni) Spinels

Abstract: The formation enthalpies from binary oxides of LiMn2 O4 , LiMn2-x Crx O4 (x=0.25, 0.5, 0.75 and 1), LiMn2-x Fex O4 (x=0.25 and 0.5), LiMn2-x Cox O4 (x=0.25, 0.5, and 0.75) and LiMn1.75 Ni0.25 O4 at 25 °C were measured by high temperature oxide melt solution calorimetry and were found to be strongly exothermic. Increasing the Cr, Co, and Ni content leads to more thermodynamically stable spinels, but increasing the Fe content does not significantly affect the stability. The formation enthalpies from oxides of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…and Li Mn O , 15b together with literature data, 38,40,44,48,49 showing good agreement. The certain deviation between the current calculation and Ren et al 40 composition where the value of 8.2427 was adopted in previous work, 19 The current work adopted the experimental results because as an endmember of the spinel model, it is consistent with the change of lattice parameter of LiNi Mn O 0.5 1.5 4 during lithiation/delithiation process, as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…and Li Mn O , 15b together with literature data, 38,40,44,48,49 showing good agreement. The certain deviation between the current calculation and Ren et al 40 composition where the value of 8.2427 was adopted in previous work, 19 The current work adopted the experimental results because as an endmember of the spinel model, it is consistent with the change of lattice parameter of LiNi Mn O 0.5 1.5 4 during lithiation/delithiation process, as shown in Fig.…”
Section: Resultssupporting
confidence: 70%
“…13c along with experimental results [43][44][45] as well as ab initio calculation. 19,38 Higher weight was given to the recent calorimetry work reported by Lai et al 44 Therefore, certain division can be observed between the current calculation and results reported by Yamaguchi et al 43 It can be observed from Fig. 13 that enthalpies of formation become less negative with increasing amount of Ni.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The newly synthesized halide under investigation in this study presents promising potential as a solid-state electrolyte in energy storage and conversion devices. The distinctive spinel structure of the material, illustrated in Figure , is renowned for its exceptional mechanical and thermal stability, making it promising for the optimal functioning of high-performance devices. , In SSEs, using octahedral primitives as the structural unit has been shown to enhance the Li-ion’s transport performance. Octahedral primitives are characterized by high symmetry and spatial structure.…”
Section: Resultsmentioning
confidence: 99%
“…Defects are crucial to the spinel's properties, and in particular can significantly increase their catalytic activity. 709,[718][719][720][721] Like perovskites, spinels are an important class of widely available, 722 thermodynamically stable, 723 relatively cost-and environmental-friendly 724 OER electrocatalysts with a well-known good efficiency. 709 Spinels are accessible via a number of methods: high-temperature solid-phase synthesis starting from metals, metal oxides, -halides, hydroxides or other salts; 725 spray pyrolysis; 706 vapor phase methods at lower temperature; 726,727 low-temperature methods are also feasible, like solution phase (sol-gel, hydrothermal-or solvothermal-) approaches 721,[728][729][730][731][732] or wet-deposition-based techniques like e.g.…”
Section: Perovskite-based Electrode Materials For Oxygen and Hydrogen...mentioning
confidence: 99%